Life fish, birds, insects, hunters &hunted. - Attenborough, David (BBC Worldwide Ltd. Program, 2010)
Fish: Fish dominate the planet's water through their astonishing vareity of shape and behavious. The beautiful weedy sea dragon looks like creaturefrom a fairytale, and the male protects their eggs by carrying then on his tail for months. The sarcastic fringehead, meanwhile, appears to turns its head inside out when it fights. Slow-motion cameras show the flying fish gliding through the air like a flock of birds and capture the world's faster swimmer, the sailfish , plucking sardines from a shoal at 70 mph. And the tiny Hawaiian goby undertakes one of nature's most daunting journeys, climbing a massive waterfall to find safe pools for breeding.